Knowledge on road traffic regulations and influence of selected socio demographic and personal factors on the knowledge among the A/L students in Jaffna educational division - Anfas, M.J.M.; Kamalarupan, L.; Coonghe, P.A.D. (University of Jaffna, 2022)
Road traffic accident is considered as one of the common public health problems around the world and it leads to fatal or non-fatal injuries. Especially younger generation gets affected to a greater extent due to the inadequate knowledge regarding road traffic regulation. This study aimed to assess the knowledge on road traffic regulations and the influence of selected socio-demographic and personal factors on the knowledge among the A/L students in Jaffna educational division. A descriptive, cross-sectional school based study was conducted among 612 A/L students in the Jaffna education Division. Ethical approval was obtained from the Ethics Review Committee, Faculty of Medicine, University of Jaffna. A pre-tested questionnaire in google form was used to collect data from the sample of 766 students and cluster sampling was used. Data were analysed by using SPSS version 25 and chi-squared test was used to describe the findings. The response rate was 79.89 %. Mean age of the study participants was 17.89 (±0.567). The majority of them were male (57.4 %) and studying in grade 13 (66.3 %). Nearly half (50.5 %) of the participants were attending school by bicycle. Around 70 % of students were known about correct side for overtaking. Most of the students were able to identify the road signs correctly. Among them 48.5% had good knowledge, 38.9 % had moderate knowledge and 12.6 % had poor knowledge on road traffic regulations. Knowledge had statistical significance with age (p < 0.001), grade (p < 0.001), able to ride (p < 0.001), having an own vehicle (p < 0.001) and having driving license (p < 0.001). The majority of the participants had good knowledge on road traffic regulations. However some students are unaware of road traffic rules and regulations and they require an educational program to improve the knowledge to reduce the chance of road traffic accident.
Keywords: Road traffic regulations; A/L Students; Knowledge; Jaffna educational division